Sistem Diagnosis Penyakit Kelamin Pada Pria Menggunakan Metode Forward Chaining Dan Dempster-Shafer - Kukuh Bhaskara; Nurul Hidayat; Lailil Muflikhah (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
According to the World Health Organization (WHO), more than 1 million sexually transmitted infections (STIs) occur every day. In one year there were an estimated 357 million new cases of sexually transmitted infections (STIs) worldwide. Sexually transmitted infections are all infections both bacteria, viruses, and fungi that are transmitted from one individual to another through sexual activity or through genital organs. For example, a newborn baby can contract gonorrhea from his mother as a result of passing through the vagina infected with N. Gonorrhoeae. According to WHO, more than 30 types of bacteria, viruses and parasites have been identified that can cause sexually transmitted diseases. 8 of these 30 species are known to have the greatest risk of causing sexually transmitted diseases. The purpose of this study was to implement the Forward Chaining and Dempster-Shafer method and testing the accuracy of the Forward Chaining and Dempster-Shafer method in identifying venereal disease in men. The results of the study shows that the accuracy of the expert system based on 35 data tested is 94.2% indicating that this expert system can function properly, namely the diagnosis of the system in accordance with expert diagnosis.